The Kingdom of Swaziland : 2006 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Swaziland's economic performance has remained weak with growth averaging only 2 percent since 2000, owing to a substantial real appreciation of the lilangeni during 2002-04, erosion of trade preferences, recurrent drought, and stagnant investment. Over that same period, rising government expenditures, especially on the wage bill, undermined fiscal sustainability and reduced foreign reserves to critically low levels. Poverty has escalated in the face of high and rising unemployment, food shortages, and the world's highest HIV/AIDS infection rate.